JayTIDS - Paul Shepheard (Oz, 1995)
Fictional narrative submitted by cultural critic Paul Shepheard in response to the editors’ theme proposal dealing with ‘Hegemony in Architecture.’ See the ‘Prologue,’ Front Matter.